Body image perception, compliance with a prosthesis and cognitive performance in transfemoral amputees - ÖZKAN, ŞÜHEDA; GÖZAYDINOĞLU, Şüheda; Hosbay, Zeynep; Durmaz, Hayati (My University, 2019)
Objective: The aim of the study was to assess mutual associations of body image perception, compliance with the prosthesis and cognitive performance in transfemoral amputees.